Intimate Language in Traditional Markets: Challenging Public Space Norms through Kristeva’s Intertextuality - Musliha, Ayu; Rosa, Dien Vidia; Prasetyo, Hery (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
The use of intimate language in public spaces is a phenomenon that emerges in the interactions of economic actors in traditional markets. Therefore, language intimacy deconstructs social norms that should not be displayed in public spaces. However, language intimacy has emerged in traditional markets for a long time in the interactions of economic actors, including sellers, buyers, porters, parking attendants, and the social gathering community. This research explores how intimate language is articulated in an economic space closely related to the ethnic identity of economic actors in traditional markets in the Jember region. The ethnic diversity in question includes Javanese, Madurese, Chinese/Chinese, and Arab. This phenomenon was researched qualitatively using a post-structuralist approach and applying Julia Kristeva's theory of intertextuality. Data analysis uses two Kristeva concepts, namely intertextuality and suprasegmental. The data is processed by looking at the text production process originating inside and outside the text. The research results show that the intimacy of language, usually used in the private sphere, has succeeded in breaking down the rigidity of language in the public sphere, besides dissolving social relations between economic actors with various ethnicities and social classes. Thus, the use of greetings in intimate language closely related to ethnic identity is experiencing development and merging with the space of familiarity and closeness built by economic actors in traditional markets.